Entertainment and entertaining in Maqasid Syariah / Halipah Hamzah - Hamzah, Halipah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
In this challenging modern age, the Muslim community, whether young or old, is stuck with the influence of Western culture namely the culture of hedonism. The goal of this culture is simply to find pleasure regardless of the legal view. Islam requires entertainment and entertaining in life. However, Islam lays down guidelines related to entertainment and entertaining to ensure that individual who entertain is not negligent. The objective of this study is to explain to the Muslim community about the law on the forms of entertainment favored by Muslims in the present century. This study also aims to clarify the guidelines of entertainment and entertaining according to Islamic law. The research question discussed in this writing is about the forms of entertainment that are prevalent in the Muslim community and its relationship with Maqasid Syariah. This study adopts data collection and data analysis methods. In an effort to collect data and information, this study is based on library research from primary and secondary sources involving Quranic sources, hadith, scholarly views, books, dictionaries, scholarly writing and journals. These data were analyzed using inductive, deductive and comparative methods. The result of the study obtained that the law of entertainment and excessive entertainment is illegal and there are guidelines and demands of Maqasid Syariah that need to be complied with in entertainment and entertaining.